Solve for y 2(y-3)-6=-5(-4y+6)-6y

Math
2(y-3)-6=-5(-4y+6)-6y
Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.
-5(-4y+6)-6y=2(y-3)-6
Simplify -5(-4y+6)-6y.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-5(-4y)-5⋅6-6y=2(y-3)-6
Multiply -4 by -5.
20y-5⋅6-6y=2(y-3)-6
Multiply -5 by 6.
20y-30-6y=2(y-3)-6
20y-30-6y=2(y-3)-6
Subtract 6y from 20y.
14y-30=2(y-3)-6
14y-30=2(y-3)-6
Simplify 2(y-3)-6.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
14y-30=2y+2⋅-3-6
Multiply 2 by -3.
14y-30=2y-6-6
14y-30=2y-6-6
Subtract 6 from -6.
14y-30=2y-12
14y-30=2y-12
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 2y from both sides of the equation.
14y-30-2y=-12
Subtract 2y from 14y.
12y-30=-12
12y-30=-12
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 30 to both sides of the equation.
12y=-12+30
Add -12 and 30.
12y=18
12y=18
Divide each term by 12 and simplify.
Tap for more steps…
Divide each term in 12y=18 by 12.
12y12=1812
Cancel the common factor of 12.
Tap for more steps…
Cancel the common factor.
12y12=1812
Divide y by 1.
y=1812
y=1812
Cancel the common factor of 18 and 12.
Tap for more steps…
Factor 6 out of 18.
y=6(3)12
Cancel the common factors.
Tap for more steps…
Factor 6 out of 12.
y=6⋅36⋅2
Cancel the common factor.
y=6⋅36⋅2
Rewrite the expression.
y=32
y=32
y=32
y=32
The result can be shown in multiple forms.
Exact Form:
y=32
Decimal Form:
y=1.5
Mixed Number Form:
y=112
Solve for y 2(y-3)-6=-5(-4y+6)-6y

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top